Tourism 4.0: Unveiling the Digital Transformation and Sustainable Development of the Tourism Industry - Shafiee, Sanaz; Rajabzadeh Ghatari, Ali (Journal of Tourism, Sustainability and Well-being, 2025)
This study aims to provide a comprehensive overview of Tourism 4.0, a concept that enhances the value of the tourism industry through innovation, technology, knowledge, and creativity. Using a systematic review approach, the research analyses selected scholarly articles to clarify definitions, explore related digital technologies, and examine the concept’s potential to support sustainable tourism development. A total of 26 articles were chosen from an initial pool of 148 based on defined quality criteria. The analysis, supported by NVivo and VOSviewer software, reveals the major themes and drivers behind Tourism 4.0, emphasising its transformative role in the tourism sector. The findings demonstrate that Tourism 4.0 can meaningfully contribute to the sustainable growth of tourism destinations by enabling digital transformation and innovation. The study identifies key research gaps and provides insights to guide future academic efforts and policymaking. By synthesising existing literature, this research offers a solid foundation for understanding Tourism 4.0 and supports informed decision-making in shaping the future of tourism through digital advancements.